2014
DOI: 10.1021/cg500006e
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Transfer Salts of Biferrocene Derivatives with F2- and F4-Tetracyanoquinodimethane: Correlation Between Donor–Acceptor Ratios and Cation Valence States

Abstract: Charge-transfer salts of biferrocene derivatives bearing branched-alkyl substituents [1′-R1-1‴-R2-1,1″-biferrocene; R1 = R2 = isopropylthio (D1), isopropyl (D2), isobutyl (D3), neopentyl (D4), and R1 = isobutyl and R2 = neopentyl (D5)] were prepared and crystallographically characterized. F2- and F4-tetracyanoquinodimethane (TCNQ) produced salts with D/A ratios of 1:3 ([D1]­[F2TCNQ]3, [D2]­[F2TCNQ]3), 1:2 ([D2]­[F4TCNQ]2, [D3]­[F4TCNQ]2), 2:3 ([D1]2­[F4TCNQ]3), and 1:1 ([D2]­[F4TCNQ], [D4]­[F2TCNQ], [D4]­[F4TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…In the case of ferrocenium salts having cyano-substituted anions, such as tetracyanoquinodimethane (TCNQ), the cyano groups of the anion are often close to the Fe atom of the cation (Fe•••N = 4.1-4.7 Å). 22 Although these distances are larger than the sum of the respective van der Waals radii, such a close arrangement is accompanied by electrostatic interactions. 22 In the case of [C0] Cations and anions often form alternating arrangements in the crystals of sandwich complex salts.…”
Section: Viscosities Of the Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of ferrocenium salts having cyano-substituted anions, such as tetracyanoquinodimethane (TCNQ), the cyano groups of the anion are often close to the Fe atom of the cation (Fe•••N = 4.1-4.7 Å). 22 Although these distances are larger than the sum of the respective van der Waals radii, such a close arrangement is accompanied by electrostatic interactions. 22 In the case of [C0] Cations and anions often form alternating arrangements in the crystals of sandwich complex salts.…”
Section: Viscosities Of the Ionic Liquidsmentioning
confidence: 99%
“…22 Although these distances are larger than the sum of the respective van der Waals radii, such a close arrangement is accompanied by electrostatic interactions. 22 In the case of [C0] Cations and anions often form alternating arrangements in the crystals of sandwich complex salts. For example, metallocenium salts containing tetracyanoethylene anions exhibit a mixedstack structure, 23 whereas those with tetracyanoquinodimethane anions exhibit both mixedand segregated-stack structures.…”
Section: Viscosities Of the Ionic Liquidsmentioning
confidence: 99%
“…atom of the cation. This close arrangement causes cation-anion electrostatic interactions, although these distances are greater than the vdW contact distance 15. In[1]X (X = B(CN)4, C(CN)3, N(CN)2), two CN groups are located close to the Fe atom.…”
mentioning
confidence: 99%
“…For 1 – 7 , the cations were located at the inversion centers, exhibiting symmetrical structures. The Fe–Cp (Cp = C 5 H 5 , centroid) distances were approximately 1.68 Å (Table 1) and were typical of biferrocenium cations undergoing rapid valence tautomerization 9a,12. The negative charges of the acceptors were estimated from the bond lengths13 and were determined to be approximately –0.5 (Table 1); therefore the dimer units have a negative charge of –1.…”
Section: Resultsmentioning
confidence: 99%
“…Several biferrocenium salts with organic acceptors have also been synthesized 5a,7. Previously, we reported the structures and electronic properties of alkyl‐ and thioalkyl‐biferrocenium salts containing F n –TCNQ (TCNQ = tetracyanoquinodimethane; n = 0, 1, 2, 4)8,9a,10 and [M(mnt) 2 ] (mnt = maleonitriledithiolate; M = Ni, Pt) 9,11. It was revealed that the valence state of the cations in these salts were dependent on the donor/acceptor (D/A) ratio.…”
Section: Introductionmentioning
confidence: 99%